PENGELOLAAN ACARA “BANDUNG LAUTAN SEPEDA” OLEH BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Putri Meysha Nabila Fauzziya; Aat Ruchiat Nugraha (Scriptura, 2020)
One of the characteristics of the success of public services carried out by an organization is in the form of delivering information and organizing an activity that is beneficial to stakeholders. Submitting information and organizing these activities is part of public communication that must be carried out by the public relations department of an organization. Is done by the Public Relations and Protocol Bureau of the Regional Secretariat of West Java Province which has the function as the front guard to provide information through various media publications with a deliberate strategy. The form of undertaken strategy is public relations events and media relations which packaged in activities with the theme "Bandung Ocean Bike". This article discusses how the contents of the communication message delivered in the "Bandung Lautan Sepeda" activity and how to use its publication media. This study uses a qualitative method with a descriptive-based research approach through data collection conducted by interviews, field observations, and literature studies. The results of the research on the "Bandung Ocean of Bicycles" activity showed that the message content conveyed on the activity poster contained persuasive sentences while the type of media publication used is below the line media such as banners, posters, backdrops, and word of mouth